2022
DOI: 10.1007/s00259-022-05778-w
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic toxicity profile and efficacy of [225Ac]Ac-PSMA-617 α-radioligand therapy of patients with extensive skeletal metastases of castration-resistant prostate cancer

Abstract: Purpose: Actinium-225-labeled prostate-specific membrane antigen ([ 225 Ac]Ac-PSMA-617) is safe and effective in the treatment of metastatic castration-resistant prostate cancer (mCRPC). No study has specifically assessed its safety in patients with extensive skeletal metastases of mCRPC. We aimed to investigate the hematologic toxicity and efficacy of [ 225 Ac]Ac-PSMA-617 therapy in patients with extensive skeletal metastases of mCRPC. Methods:We retrospectively reviewed the medical record of patients treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Of the included 14 series, 5 did not report outcomes of interest according to the prior status on 177Lu‐PSMA TRT 32–35 ; and, hence, also had the lowest scores on the Newcastle−Ottawa scale. However, of the studies that underwent quantitative analysis, the score ranged between 5 and 8 with most of them having good quality (e.g., scored 3 or 4 stars in the selection domain and 1 or 2 stars in comparability and 2 or 3 stars in the outcome category) (Table 7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the included 14 series, 5 did not report outcomes of interest according to the prior status on 177Lu‐PSMA TRT 32–35 ; and, hence, also had the lowest scores on the Newcastle−Ottawa scale. However, of the studies that underwent quantitative analysis, the score ranged between 5 and 8 with most of them having good quality (e.g., scored 3 or 4 stars in the selection domain and 1 or 2 stars in comparability and 2 or 3 stars in the outcome category) (Table 7).…”
Section: Resultsmentioning
confidence: 99%
“…Of the included 14 series, 5 did not report outcomes of interest according to the prior status on 177Lu-PSMA TRT [32][33][34][35] ; and, hence, also had the lowest scores on the Newcastle−Ottawa scale.…”
Section: Qualitative Analysismentioning
confidence: 99%
“…In a retrospective study of patients treated with 225 Ac PSMA-617, 106 patients were found to have either multifocal (≥20) skeletal metastases (n = 72, 67.9%), or a diffuse pattern of axial skeletal involvement with or without appendicular skeletal involvement (i.e., superscan pattern) on 68 Ga PSMA-11. Eighty-five of the 106 patients (80.2%) treated with 225 Ac PSMA-617 achieved a PSA response of ≥50% and had only rare hematologic toxicity with renal dysfunction being a significant risk factor [ 55 ]. As 225 Ac/ 177 Lu-PSMA radiopharmaceuticals have different benefits and risks, small trials have also incorporated a “tandem” therapy strategy with small doses of 225 Ac-PSMA being administered together with 177 Lu-PSMA and with promising results [ 56 ].…”
Section: Alpha Emitting Psma Targeted Radiotherapeuticsmentioning
confidence: 99%
“…In retrospective study of patient's treated with 225 Ac PSMA-617, 106 patients were found to have either multifocal (≥ 20) skeletal metastases (n=72, 67.9%), or a diffuse pattern of axial skeletal involvement with or without appendicular skeletal involvement (i.e., superscan pattern) on 68 Ga PSMA-11. Eighty-five of the 106 patients (80.2%) treated with 225 Ac PSMA-617 achieved a PSA response of ≥50% and had only rare hematologic toxicity with renal dysfunction being a significant risk factor [49]. As 225 Ac/ 177 Lu-PSMA radiopharmaceuticals have different benefits and risks, small trials have also incorporated a "tandem" therapy strategy with small doses of 225 Ac-PSMA being administered together with 177 Lu-PSMA and with promising results [50].…”
Section: Alpha Emitting Psma Targeted Radiotherapeuticsmentioning
confidence: 99%